Computer modeling of crystallization processes as a reserve of improving the quality of pistons of ICE - Пономаренко, Ольга Ивановна; Тренёв, Николай Сергеевич (Technology audit and production reserves, 2013)
The use of pattern recognition procedure for the description of the localization of defects in the molded pieces "piston" for ICE (internal combustion engine) is proposed in the paper. The relevance of this research is explained by the need of rapid development of new high quality molded pieces for the automotive industry, or optimization of the existing equipment design to improve the product quality. The results of computer modeling of the process of metal mold casting and alloy crystallization for the advanced casting technology, involving the use of thermal insulating coatings of metal mold are given. The results of computer modeling can be used for formalization of the process of describing the localization of defects in pistons and, based on this, for development of measures on resource saving and improving the quality of molded pieces. It was proposed to use the results of statistical classification on the basis of such formalized description.